Exclusive Drug Labeling Rights as a New Incentive for Contribution to a Communal Biomarker Resource. Issue 4 (November 2018) - Shore, David
Biomarkers are an important tool in modern drug development. The FDA has posited that increased use of biomarkers in clinical trials can accelerate pharmaceutical industry productivity, ushering new drugs to market. Accordingly, the FDA has created two pathways for evaluation of biomarker utility. Biomarkers incorporated into clinical trials, the traditional pathway, are effectively private to a therapeutic sponsor and to the scope of the trial. By contrast, in Biomarker Qualification ("BQ"), the second pathway, a biomarker is certified as a publicly available tool. The FDA has hoped that academic, non-profit, and industry stakeholders would work together in consortia to qualify biomarkers, cumulatively generating a common resource of broad utility. In practice, utilization of Biomarker Qualification has been paltry. Incentives for BQ that align with the interests of industry resource holders are necessary to fuel increased utilization of biomarkers in clinical trials and create the communal biomarker toolkit envisioned by the FDA. A blanket extension of exclusivity for any drug successfully paired with a companion biomarker would diminish public access to medicine by encouraging spurious biomarkers and correspondingly narrowed clinical trials. As a measured alternative, an exclusive right to include a qualified companion biomarker on an FDA drug label would balance public access externalities. This exclusivity would waylay label approval, and thus marketability, of later drugs relying on the qualified biomarker for clinical safety or efficacy. Accordingly, sponsors would find no incentive to portage an ineffective or unnecessary biomarker through clinical trials, as there would be no benefit to securing exclusive rights in a tool others saw no value in using.